FORMULATION OF FIBER RICH TORTILLA CHIPS (SNACK) USING PSYLLIUM HUSK - Vaibhav Raju Bage; Iranna S. Udachan; Akshaya Kumar Sahoo (The Bioscan, 2025)
Snacks are a convenient substitute for traditional meals. Corn flour is the traditional ingredient used to make tortilla chips. The high calcium, iron, and dietary fiber content of Ragi makes it stand out. The utilization of Psyllium husk in various cultures has been traditional for its medicinal purposes. A rise in the consumption of healthy foods is necessary to lower the risks of chronic diseases. The aim of this research was to create a snack product that is rich in fiber. The objective of this research was to develop a tortilla chip that has a high amount of nutrients by incorporating Psyllium husk. The experiment involved making tortilla chips by substituting corn flour with Psyllium husk in different proportions. After preparing Tortilla chips, the sensory quality was assessed. In this investigation, attempts have been made to develop fried snacks from corn, ragi, psyllium husk, red chili powder, salt, and turmeric etc. Tortilla chips were prepared using the methodology provided by Bage V. R. et al, (2023). Two steps were involved in the preparation process: masa flour preparation and tortilla chip preparation. Tortilla Chips were deep-fat fried by using cottonseed oil at 180℃ for 2-3 min in a fryer. The sensory analysis led to the formulation of a composite flour that contains corn and ragi in an 80:20 ratio to supplement tortilla chips. The inclusion of Psyllium husk (3%) resulted in the addition of nutritional value and improved the quality of tortilla chips. Thus, the study succeeded in creating fiber-rich tortilla chips that have a good nutritional profile. Nutritionally and health-wise, the developed product was superior to standard tortilla chips. The future market would be greatly influenced by fiber-rich tortilla chips.